1973
DOI: 10.1021/jo00965a006
|View full text |Cite
|
Sign up to set email alerts
|

Dimetalated heterocycles as synthetic intermediates. IV. Dilithio derivatives of 2-methylbenzimidazole, 2-benzylbenzimidazole, and related compounds

Abstract: Treatment of 2-methylbenzimidazole (la), 2-methyl-5-chlorobenzimidazole (Ib), 2-benzylbenzimidazole (IC), and l-(2-benzimidazolyl)-I-phenylpropane (3g) with 2 mol equiv of n-butyllithium in THF-hexane at 0" resulted in abstraction of the heterocyclic NH proton as well as an 01 hydrogen of the 2-alkyl substituent. Reactions of the resulting dilithio derivatives with alkyl halides, aldehydes, and ketones took place selectively at the sidechain carbanion center to produce 2-alkylbenzimidazoles and 2-(2-hydroxylal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

1974
1974
2002
2002

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…described the metallation of the 2-methyl position of 2-methylbenzimidazole by treat-ment of the parent compound with n-butyllithium. 10 Comparison of the conditions required to metallate the 2methyl position indicated that N-alkylation could be accomplished without metallation occurring at the 2-methyl position. After the acidic N-H of the heterocycle has been replaced with an alkyl group, a strong base can be used to metallate the 2-methyl position exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…described the metallation of the 2-methyl position of 2-methylbenzimidazole by treat-ment of the parent compound with n-butyllithium. 10 Comparison of the conditions required to metallate the 2methyl position indicated that N-alkylation could be accomplished without metallation occurring at the 2-methyl position. After the acidic N-H of the heterocycle has been replaced with an alkyl group, a strong base can be used to metallate the 2-methyl position exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…[432] Scheme 53 Replacement of an á-Hydrogen [432] for references see p 602 [432] Scheme 53 Replacement of an á-Hydrogen [432] for references see p 602…”
Section: Modification Of Substituents On a Ring Carbonmentioning
confidence: 99%
“…Reaction of the dianion of 1,1-diphenylacetone (1) with benzophenone (2a) or bis(p-tolyl) ketone (2b) and subsequent addition of diethylmalonic dichloride afforded the eight-membered 1,5-dioxocane-2,4-diones 5a and 5b, respectively, in good yields (Scheme 2). Reaction of the dianion of 2-methylbenzimidazole (6), [15] …”
mentioning
confidence: 99%
“…Reaction of the dianion of 1,1-diphenylacetone (1) with benzophenone (2a) or bis(p-tolyl) ketone (2b) and subsequent addition of diethylmalonic dichloride afforded the eight-membered 1,5-dioxocane-2,4-diones 5a and 5b, respectively, in good yields (Scheme 2). Reaction of the dianion of 2-methylbenzimidazole (6), [15] (an aza analogue of 1) with benzophenone, and subsequent treatment with oxalyl chloride resulted in the release of CO, [16] and in the formation of the 3,4-dihydrobenzo [4,5]imidazo [1,2-c] [1,3]oxazin-1-one (7) (Scheme 3). Oxazepins are known to undergo decarbonylation reactions at elevated temperatures, and have been used for the synthesis of reserpine alkaloids.…”
mentioning
confidence: 99%